Application of Analytic Hierarchy Process (AHP) in Evaluating the Achievement Level of Objectives of Urban Development Plan (International Journal of Built Environment and Sustainability, 2016)
Planning evaluation can be a systematic assessment of plans, planning processes, objectives and outcomes compared with explicit standards or indicators. Evaluating the achievement level of objectives of development plan has been ignored in the field of planning due to lack of proper method. But in practice, these evaluations are complicated because objectives are not always clear and measurable. Therefore this study is supposed to evaluate the level of achievement of objectives of the development plan by applying Analytic Hierarchy Process (AHP) when objectives are not measurable. Public perception on achievement of objectives criteria of related action projects considering overall benefits of each project were judged as ex post facto evaluation. Field surveys and questionnaire surveys were carried out to identify different views of different stakeholders. This application can be used as an objective evaluation tool for planners and policy makers to improve planning practices and provide necessary knowledge for revising plans.